Congenital pulmonary airway malformation - Tasayco Saravia, Juan Carlos (2020)
Congenital pulmonary airway malformation (MCVAP), formerly known as congenital cystic adenomatoid pulmonary malformation (MAQP), belongs to the group of congenital pulmonary malformations, representing 95% of these. It is characterized by varying degrees of respiratory distress according to the level of the airway that compromises the injury and may be incompatible with life until it goes unnoticed until early adulthood. Advances in molecular biology have discovered that there is an imbalance between proliferating and apoptotic genes within these lesions, disrupting the segmentation of the bronchial tree, triggering the formation of these lesions. On the other hand, advances in fetal ultrasound have allowed 50% of cases to be detected from fetal life, causing these children to have their lesions removed during the first weeks of life and their improved life prognosis. This literary review seeks to update concepts on the latest discoveries in the pathophysiology, detection and management of MCVAP.